Open-Wedge High Tibial Osteotomy Associated With Lipogems® Intra-Articular Injection For The Treatment Of Varus Knee Osteoarthritis – Retrospective Study - Magnanelli, Stefano; Screpis, Daniele; Di Benedetto, Paolo; Natali, Simone; Causero, Araldo; Zorzi, Claudio (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Open-wedge high tibial osteotomy (HTO) is a good choice in the treatment of varus knee medial osteoarthritis, with the restore of the correct mechanical axis of the lower limb. Autologous adipose derived stem cells (aASCs) are used in cartilage regeneration and in the treatment of early osteoarthritis. Aim of this study is to retrospectively analyze clinical (and radiological) results in two populations of patients with initial varus medial knee osteoarthritis, treated with HTO, with or without associated intra-articular injection of aASCs.Methods: In this study we analyze 85 patients treated with HTO for varus knee osteoarthritis with or without Lipogems® intra-articular injection. It was used of a single model of HTO plate. No associated procedure was performed.Results: Significant improvement in the daily life activity assessment (KOOS score) was observed in the group treated also with aASCs compared with group treated with isolated HTO.Conclusions: We suggest, in these patients, the surgical indication of an open-wedge high tibial osteotomy (HTO) and simultaneous injection with aASCs associated procedure to improve cartilage regeneration, with clinical improvement